Iron-based amorphous nanocrystalline alloy, its application and preparation method
By adjusting the element types and percentage content in the iron-based amorphous nanocrystalline alloy, the problem of insufficient saturation magnetic induction strength of Finemet alloy is solved, and an iron-based amorphous nanocrystalline alloy with high effective magnetic permeability and low coercive force is achieved, which is suitable for the miniaturization and efficiency of electronic components.
Patent Information
- Application Number
- CN202210511034.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-05-11
AI Technical Summary
The existing Finemet alloys have insufficient saturation magnetic induction strength while maintaining effective magnetic permeability, low coercivity and low loss, making it difficult to meet the needs of miniaturization and efficiency of electronic components.
By adjusting the element types and percentage content in the iron-based amorphous nanocrystalline alloy, an iron-based amorphous nanocrystalline alloy of FeaCobMocCudNbeSifBg or FeaCobMocCudNbeSifBgMh was prepared to ensure that the atomic percentage of iron is between 70 and 82, the total atomic percentage of Si and B is between 20 and 25, and the atomic percentage ratio of Si and B is between 1 and 3.
It improves the saturated magnetic induction strength and effective magnetic permeability of iron-based amorphous nanocrystalline alloys, while maintaining low coercive force and low loss, improving its comprehensive performance.
Smart Images

Figure CN114864210B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal materials, and in particular to an iron-based amorphous nanocrystalline alloy, its application and a preparation method thereof. Background Art
[0002] Since the discovery of amorphous alloys in the 1960s, amorphous alloys have experienced rapid development. In 1988, Yoshizawa et al. of Hitachi Metals of Japan discovered Fe with excellent soft magnetic properties. 73.5 Si 13.5 B9Nb3Cu1 nanocrystalline alloy, named Finemet (i.e. domestic commercial grade 1K107), has created a new situation for the application of amorphous alloys. Finemet alloy can be used to make mutual inductors, common mode inductors, inverters and other magnetic electronic components.
[0003] With the further requirements for miniaturization and high efficiency of electronic components, the shortcomings of Finemet alloy are gradually becoming apparent. The industry is in urgent need of new nanocrystalline alloy materials to improve the saturation magnetic induction intensity of Finemet alloy while maintaining its effective magnetic permeability, low coercive force and low loss. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing an iron-based amorphous nanocrystalline alloy, its application and its preparation method, so as to improve its saturation magnetic induction intensity while maintaining the effective magnetic permeability, low coercive force and low loss of the iron-based amorphous nanocrystalline alloy.
[0005] In a first aspect, the present invention provides an iron-based amorphous nanocrystalline alloy, the chemical formula of the iron-based amorphous nanocrystalline alloy is: Fe a Co b Mo c Cu d Nb e Si f B g ; Wherein, a, b, c, d, e, f, g are the atomic percentages of the corresponding elements, 70≤a≤82, 0<b≤6, 0<c≤6, 0<b+c≤6, 0<d≤2, 0<e≤5, 11≤f≤18, 5≤g≤13, 20≤f+g≤25, f:g=(1~3):1, and a+b+c+d+e+f+g=100.
[0006] The inventors have found that the elements in the iron-based amorphous nanocrystalline alloy are Fe, Co, Mo, Cu, Nb, Si and B, and the atomic percentage of iron is between 70 and 82, the total atomic percentage of Si and B is between 20 and 25, and the atomic percentage ratio of Si to B is between 1 and 3, which can make its effective magnetic permeability higher, the coercive force smaller, and the saturation magnetic induction intensity larger, so that the comprehensive performance of the iron-based amorphous nanocrystalline alloy is better.
[0007] In some embodiments of the present application, 73≤a≤76, 1≤b+c≤4, f:g=(1.5~2.5): 1. The coercivity of the iron-based amorphous nanocrystalline alloy can be further reduced, and the effective magnetic permeability of the iron-based amorphous nanocrystalline alloy can be improved.
[0008] In some embodiments of the present application, b:c=(0.5-1.5):(0.5-1.5), d:f=1:(13-15).
[0009] In some embodiments of the present application, the chemical formula of the iron-based amorphous nanocrystalline alloy is Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 13 B8 or Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 15 B6. The iron-based amorphous nanocrystalline alloy has good performance and is suitable for industrial production.
[0010] In a second aspect, the present application provides an iron-based amorphous nanocrystalline alloy, the chemical formula of the iron-based amorphous nanocrystalline alloy is: Fe a Co b Mo c Cu d Nb e Si f B g M h ; Wherein, M is one or a combination of Zr, V, Al, Ni, Ta, W, Hf, Cr, Mn, Ti, P, C, O, S, H, and rare earth elements; a, b, c, d, e, f, g, and h are the atomic percentages of the corresponding elements, 70≤a≤82, 0<b≤6, 0<c≤6, 0<b+c≤6, 0<d≤2, 0<e≤5, 11≤f≤18, 5≤g≤13, 20≤f+g≤25, f:g=(1~3):1, h≤0.1, and a+b+c+d+e+f+g+h=100.
[0011] In the present application, a small amount of other elements M (the amount added is not more than 0.1%) is added to the iron-based amorphous nano alloy, which basically does not affect the performance of the material, and the performance of the material is also relatively excellent.
[0012] In some embodiments of the present application, 73≤a≤76, 1≤b+c≤4, f:g=(1.5~2.5):1.
[0013] In some embodiments of the present application, b:c=(0.5-1.5):(0.5-1.5), d:f=1:(13-15).
[0014] In a third aspect, the present application provides an iron-based amorphous nanocrystalline alloy sheet, wherein the material of the iron-based amorphous nanocrystalline sheet is the above-mentioned iron-based amorphous nanocrystalline alloy. Since the above-mentioned iron-based amorphous nanocrystalline alloy has good comprehensive performance, the sheet structure prepared by the above-mentioned iron-based amorphous nanocrystalline alloy also has good comprehensive performance.
[0015] In some embodiments of the present application, the thickness of the iron-based amorphous nanocrystalline alloy sheet is 17-21 μm, the saturation magnetic induction intensity is 1.39-1.41 T, the coercive force is 1.4-1.5 A / m, the effective magnetic permeability is greater than 20,000 at 100 kHz, and the effective magnetic permeability is greater than 6,000 at 1 MHz.
[0016] In a fourth aspect, the present application provides an application of an iron-based amorphous nanocrystalline alloy sheet in preparing a magnetic isolation sheet for a wireless charging device. The use of the iron-based amorphous nanocrystalline alloy sheet as a magnetic isolation sheet can make the charging of the wireless charging device faster and is conducive to the miniaturization of electronic devices.
[0017] In a fifth aspect, an embodiment of the present application provides a method for preparing an iron-based amorphous nanocrystalline alloy, wherein the iron-based amorphous nanocrystalline alloy is a strip, and the preparation method comprises: according to the content of various elements in the chemical formula of the iron-based amorphous nanocrystalline alloy, various raw materials are weighed in mass percentage and mixed to obtain a mixed raw material. The mixed raw material is smelted to obtain an alloy liquid and sprayed onto the surface of a metal roller to obtain an iron-based amorphous alloy strip. The iron-based amorphous alloy strip is subjected to transverse magnetic annealing to obtain an iron-based amorphous nanocrystalline alloy strip.
[0018] The strips prepared by the method are suitable for industrial production, and after production, the performance of the strips obtained is better.
[0019] In some embodiments of the present application, the rotation speed of the metal roller is 30-40 m / s.
[0020] In some embodiments of the present application, the transverse magnetic annealing conditions are: heat treatment for more than 60 minutes under nitrogen protection, magnetic field of 0.05-0.1T, temperature of 540-580°C, etc. It is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A process flow chart for preparing a strip of an iron-based amorphous nanocrystalline alloy provided in an embodiment of the present application;
[0023] Figure 2 The DSC curve of the iron-based amorphous nanocrystalline alloy provided in Example 2;
[0024] Figure 3 BH curves of the iron-based amorphous nanocrystalline alloys provided in Example 1 and Example 2;
[0025] Figure 4 The effective magnetic permeability curve of the iron-based amorphous nanocrystalline alloy provided in Example 1 and Example 2;
[0026] Figure 5 The magnetic domain photos of the cast and transverse magnetic annealed iron-based amorphous nanocrystalline alloy provided in Example 2;
[0027] Figure 6 This is a transverse magnetic annealing TEM photo of the iron-based amorphous nanocrystalline alloy provided in Example 2;
[0028] Figure 7 This is a graph showing the concentration of nanocrystalline elements in the iron-based amorphous nanocrystalline alloy provided in Example 2;
[0029] Figure 8 The nanocrystalline element concentration analysis diagram of the iron-based amorphous nanocrystalline alloy provided in Comparative Example 1;
[0030] Fig. 9 The XRD diagram of the iron-based amorphous nanocrystalline alloy provided in Example 2 during industrial production;
[0031] Fig.10 This is a photo of the industrially produced strip of the iron-based amorphous nanocrystalline alloy provided in Example 2. DETAILED DESCRIPTION
[0032] In the prior art, the parameters for evaluating the performance of iron-based amorphous nanocrystalline alloys generally include saturation magnetic induction, coercivity and effective magnetic permeability. In order to improve the comprehensive performance of iron-based amorphous nanocrystalline alloys, different elements are usually added to the iron-based amorphous nanocrystalline alloys for processing.
[0033] However, the inventors have found that, in general, by adding different elements, one property of the iron-based amorphous nanocrystalline alloy can be improved, but the overall performance cannot be improved. In this application, on the one hand, the inventors adjust the element types of the iron-based amorphous nanocrystalline alloy, and on the other hand, limit the percentage content of several elements therein, so that the overall performance of the iron-based amorphous nanocrystalline alloy can be better (higher saturation magnetic induction intensity and effective magnetic permeability, lower coercive force).
[0034] The present application provides an iron-based amorphous nanocrystalline alloy, the chemical formula of which is: Fe a Co b Mo c Cu d Nb e Si f B g ; Wherein, a, b, c, d, e, f, g are the atomic percentages of the corresponding elements, 70≤a≤82, 0<b≤6, 0<c≤6, 0<b+c≤6, 0<d≤2, 0<e≤5, 11≤f≤18, 5≤g≤13, 20≤f+g≤25, f:g=(1~3):1, and a+b+c+d+e+f+g=100.
[0035] The inventors have found that the elements in the iron-based amorphous nanocrystalline alloy are Fe, Co, Mo, Cu, Nb, Si and B, and the atomic percentage of iron is between 70 and 82, the total atomic percentage of Si and B is between 20 and 25, and the atomic percentage ratio of Si to B is between 1 and 3, which can make its effective magnetic permeability higher, the coercive force smaller, and the saturation magnetic induction intensity larger, so that the comprehensive performance of the iron-based amorphous nanocrystalline alloy is better.
[0036] Optionally, 73≤a≤76, 1≤b+c≤4, f:g=(1.5~2.5):1. Further, d:f=1:(13~15), b:c=(0.5~1.5):(0.5~1.5).
[0037] In some embodiments, the iron-based amorphous nanocrystalline alloy has a chemical formula of Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 13 B8 or Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 15 B6.
[0038] In other embodiments, the iron-based amorphous nanocrystalline alloy has a chemical formula of Fe 73Co3Mo 0.5 Cu1Nb 1.5 Si 13 B8, Fe 72 Co4Mo 0.5 Cu1Nb 1.5 Si 13 B8, Fe 75 Co1Mo 0.5 Cu1Nb 1.5 Si 13 B8, Fe 74 Co1Mo 0.5 Cu1Nb 1.5 Si 14 B8, Fe 74 Co1Mo 0.5 Cu1Nb 2.5 Si 13 B8, Fe 74 Co1Mo 0.5 Cu4Nb 1.5 Si 13 B8, etc.
[0039] The above-mentioned iron-based amorphous nanocrystalline alloy can be a sheet or a strip. Since the above-mentioned iron-based amorphous nanocrystalline alloy has good comprehensive properties, the sheet structure prepared by using it also has good comprehensive properties.
[0040] The thickness of the sheet or strip of the iron-based amorphous nanocrystalline alloy is 17-21 μm, the saturation magnetic induction intensity is 1.39-1.41 T, the coercive force is 1.4-1.5 A / m, the effective magnetic permeability is greater than 20000 at 100 kHz, and the effective magnetic permeability is greater than 6000 at 1 MHz. The sheet or strip of the iron-based amorphous nanocrystalline alloy that meets the above performance can be used to prepare the magnetic isolation sheet of the wireless charging device. Its use as a magnetic isolation sheet can make the charging of the wireless charging device faster and is conducive to the miniaturization of electronic equipment.
[0041] For example, for display devices such as wireless charging mobile phones or tablets, the magnetic isolation sheets at the receiving end of the display device or the transmitting end of the charger can be prepared using the sheets or strips of the above-mentioned iron-based amorphous nanocrystalline alloy, thereby improving the charging efficiency and making the device more miniaturized.
[0042] The preparation method of the above-mentioned iron-based amorphous nanocrystalline alloy strip is as follows: Figure 1 For the preparation process flow chart of the iron-based amorphous nanocrystalline alloy strip provided in the embodiment of the present application, please refer to Figure 1 , the preparation method comprises:
[0043] S110, preparing mixed raw materials: according to the contents of various elements in the chemical formula of the iron-based amorphous nanocrystalline alloy, various raw materials in mass percentage are weighed and mixed to obtain a mixed raw material.
[0044] S120, smelting a master alloy: smelting the mixed raw material to obtain a molten alloy and cooling it to obtain a master alloy ingot. The smelting may be performed multiple times, and slag removal may be performed each time the smelting is performed to obtain a master alloy ingot with higher purity.
[0045] S130, preparing iron-based amorphous nanocrystalline strips: melting the master alloy ingot to obtain alloy liquid and spraying the alloy liquid onto the surface of the metal roller to obtain the iron-based amorphous alloy strips. The rotation speed of the metal roller is 30-40 m / s.
[0046] Optionally, the metal roller is a copper roller, which may be made entirely of copper material or may be a roller structure having a copper layer on the surface.
[0047] S140, performing transverse magnetic annealing on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic annealing conditions are: heat treatment for more than 60 minutes under nitrogen protection, a magnetic field of 0.05-0.1T, and a temperature of 540-580°C, which is suitable for industrial production.
[0048] In other embodiments, the heat treatment may be performed in a vacuum environment at a temperature of 480 to 580° C. for 10 to 40 minutes. In a vacuum environment, the heat treatment time may be reduced.
[0049] The iron-based amorphous nanocrystalline alloy strips obtained by the above method have better comprehensive performance and can be used to prepare magnetic isolation sheets in wireless charging devices. They have good charging effects and are conducive to the miniaturization of the equipment.
[0050] In the present application, the iron-based amorphous nanocrystalline alloy is not limited to the above-mentioned Fe, Co, Mo, Cu, Nb, Si and B elements, and a small amount of other elements may be added, which will not affect the performance of the alloy. The chemical formula of the iron-based amorphous nanocrystalline alloy is: Fe a Co b Mo c Cu d Nb e Si f B g M h; Wherein, M is one or a combination of Zr, V, Al, Ni, Ta, W, Hf, Cr, Mn, Ti, P, C, O, S, H, and rare earth elements; a, b, c, d, e, f, g, and h are the atomic percentages of the corresponding elements, 70≤a≤82, 0<b≤6, 0<c≤6, 0<b+c≤6, 0<d≤2, 0<e≤5, 11≤f≤18, 5≤g≤13, 20≤f+g≤25, f:g=(1~3):1, h≤0.1, and a+b+c+d+e+f+g+h=100.
[0051] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below. If the specific conditions are not specified in the embodiments, they are carried out according to the conditions recommended by the normal conditions or the manufacturers. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0052] Example 1
[0053] Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 13 The preparation method of B8 amorphous nanocrystalline alloy comprises:
[0054] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0055] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0056] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0057] The effective magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, B sThe 7410 vibrating sample magnetometer produced by Lake Shore, USA, was used for measurement. The sample was selected as 2 to 3 amorphous strips with a length of about 4 mm, and was weighed repeatedly 3 times with a high-precision electronic balance (accuracy: 0.01 mg). The sample was attached to the bottom of the circular sample stage with double-sided tape and kept parallel to the test magnetic field along the length direction. The maximum applied magnetic field was 800 kA / m. c The measurement was performed using the EXPH-100 DC magnetic characteristics analyzer (DCB-H Curve Tracer) produced by RIKEN, Japan. The maximum applied magnetic field was 800A / m, and the sample length was uniformly 8cm to ensure that the sample pasting method was consistent and in the center of the solenoid. e The impedance analyzer E4990A produced by Keysight was used for measurement. The maximum external magnetic field was 1A / m and the sample length was about 6cm. s 1.41T, H c It is 1.4A / m, the effective magnetic permeability is 20010 at 100kHz, and the effective magnetic permeability is 6218 at 1MHz.
[0058] Example 2
[0059] Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 15 The preparation method of B6 amorphous nanocrystalline alloy comprises:
[0060] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0061] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0062] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0063] The magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, its B s 1.39T, H cIt is 1.5A / m, the effective magnetic permeability is 20200 at 100kHz, and the effective magnetic permeability is 6310 at 1MHz.
[0064] Example 3
[0065] Fe 73 Co3Mo 0.5 Cu1Nb 1.5 Si 13 The preparation method of B8 amorphous nanocrystalline alloy comprises:
[0066] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0067] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0068] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0069] The magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, its B s 1.39T, H c It is 2.5A / m, the effective magnetic permeability is 18400 at 100kHz, and the effective magnetic permeability is 7900 at 1MHz.
[0070] Comparative Example 1
[0071] Fe 76 Mo 0.5 Cu1Nb 1.5 Si 13 The preparation method of B8 amorphous nanocrystalline alloy comprises:
[0072] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0073] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0074] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0075] The magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, its B s 1.37T, H c It is 3.7A / m, the effective magnetic permeability is 13200 at 100kHz, and the effective magnetic permeability is 5260 at 1MHz.
[0076] Comparative Example 2
[0077] Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 11 B 10 The preparation method of the amorphous nanocrystalline alloy comprises:
[0078] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0079] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0080] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0081] The magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, its B s 1.37T, H c It is 3.7A / m, the effective magnetic permeability is 13200 at 100kHz, and the effective magnetic permeability is 5260 at 1MHz.
[0082] Comparative Example 3
[0083] Fe 75.5 Co 0.5 Mo0.5 Cu1Nb 1.5 Si8B 13 The preparation method of the amorphous nanocrystalline alloy comprises:
[0084] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0085] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0086] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0087] The magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, its B s 1.38T, H c It is 3.6A / m, the effective magnetic permeability is 13000 at 100kHz, and the effective magnetic permeability is 5020 at 1MHz.
[0088] Comparative Example 4
[0089] Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 14 B 7.5 Cr 0.5 The preparation method of the amorphous nanocrystalline alloy comprises:
[0090] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0091] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0092] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0093] The magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, its B s 1.35T, H c It is 2.3A / m, the effective magnetic permeability is 15500 at 100kHz, and the effective magnetic permeability is 5988 at 1MHz.
[0094] Comparative Example 5
[0095] Fe 78 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 13 B 5.5 The preparation method of the amorphous nanocrystalline alloy comprises:
[0096] (1) Weigh and prepare the ingredients according to the alloy chemical formula, and repeatedly melt the ingredients until the master alloy components are melted evenly.
[0097] (2) The smelted master alloy is induction heated to a molten state to obtain alloy liquid, which is quickly sprayed onto the surface of a rapidly rotating copper roller to obtain an iron-based amorphous strip with a width of 1 mm and a thickness of 21 μm. The rotation speed of the copper roller is 30 to 40 m / s.
[0098] (3) Performing transverse magnetic heat treatment on the iron-based amorphous alloy strip to obtain an iron-based amorphous nanocrystalline alloy strip. The transverse magnetic heat treatment conditions are: heat treatment for 30 minutes under the conditions of a magnetic field intensity of 0.1T and a temperature of 560°C in a vacuum environment.
[0099] The magnetic permeability μ of the obtained nanocrystalline alloy strips was e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, its B s 1.45T, H c It is 3.2A / m, the effective magnetic permeability is 11000 at 100kHz, and the effective magnetic permeability is 3200 at 1MHz.
[0100] Figure 2 The DSC curve of the iron-based amorphous nanocrystalline alloy provided in Example 2; Figure 2 It can be seen that the first crystallization temperature T x1 is 478°C, the second crystallization temperature T x2 640℃, indicating that this component has high thermal stability and a wide thermal treatment process window (ΔT x =162°C).
[0101] Figure 3 The BH curves of the iron-based amorphous nanocrystalline alloys provided in Example 1 and Example 2; Figure 3 It can be seen that the saturation magnetic induction intensity values of the two iron-based amorphous nanocrystalline alloys are both large and have better performance.
[0102] Figure 4 The effective magnetic permeability curve of the iron-based amorphous nanocrystalline alloy provided in Example 1 and Example 2; Figure 4 It can be seen that the effective magnetic permeability of the iron-based amorphous nanocrystalline alloy provided in Example 1 is 20010 at 100kHz, and the effective magnetic permeability of the iron-based amorphous nanocrystalline alloy provided in Example 2 is 20200 at 100kHz; the effective magnetic permeability of the iron-based amorphous nanocrystalline alloy provided in Example 1 is 6218 at 1MHz, and the effective magnetic permeability of the iron-based amorphous nanocrystalline alloy provided in Example 2 is 6310 at 1MHz, and its performance is better.
[0103] Figure 5 The magnetic domain photos of the cast and transverse magnetic annealing of the iron-based amorphous nanocrystalline alloy provided in Example 2; Figure 5 It can be seen that compared with the irregular, small-scale, multi-branched domains in the cast sample, the magnetic domains after transverse magnetic heat treatment, the smooth edges and wide stripe domains can essentially reflect the low pinning effect and low magnetic anisotropy of the amorphous nanocrystalline samples, showing good soft magnetic properties.
[0104] Figure 6 TEM photo of the transverse magnetic annealing of the iron-based amorphous nanocrystalline alloy provided in Example 2; Figure 6 It can be seen that after transverse magnetic annealing, uniform α-Fe nanocrystals are precipitated from the amorphous matrix, forming an amorphous-nanocrystalline composite structure with excellent soft magnetic properties. The nanocrystals are small in size, with an average size of only 11.89 nm. Generally speaking, the finer and more uniform the nanocrystals precipitated from the amorphous matrix, the better the soft magnetic properties of the nanocrystalline alloy.
[0105] Figure 7 This is a graph showing the concentration of nanocrystalline elements in the iron-based amorphous nanocrystalline alloy provided in Example 2. Figure 8 The nanocrystalline element concentration analysis diagram of the iron-based amorphous nanocrystalline alloy provided in Comparative Example 1 is as follows: Figure 7 It can be inferred that in Example 2, during transverse magnetic annealing, the Fe and Co coupling induced magnetic inhomogeneity, promoted the generation of nucleation points, increased the density of nucleation points, and formed finer and more uniform α-Fe nanocrystals. This fine amorphous-nanocrystalline dual-phase structure exhibited more excellent soft magnetic properties and improved the effective magnetic permeability of the material. Figure 8It can be seen that the iron-based amorphous nanocrystalline alloy provided in Comparative Example 1 is similar to the Finemet alloy. When other nanocrystalline alloys such as Finemet are annealed, Cu atoms are segregated to generate nucleation points, and then α-Fe nanocrystals are precipitated to form a nanocrystalline alloy.
[0106] The compositions and properties of the iron-based amorphous nanocrystalline alloy strips provided in Examples 1 to 3 and Comparative Examples 1 to 5 are shown in Table 1.
[0107] Table 1 Composition and properties of Fe-based amorphous nanocrystalline alloy strips
[0108]
[0109] It can be seen from Table 1 that the comprehensive performance of the iron-based amorphous nanocrystalline alloy strips provided by Examples 1 to 3 is good, especially the comprehensive performance of the iron-based amorphous nanocrystalline alloy strips provided by Examples 1 and 2 is better.
[0110] From the comparison between Example 1 and Comparative Example 1, it can be seen that in addition to the elements Fe, Mo, Cu, Nb, Si and B (the addition amounts of various elements in Example 1 and Comparative Example 1 are basically the same), the iron-based amorphous nanocrystalline alloy also contains the element Co, which can make the saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy strips higher, the coercive force smaller, the effective magnetic permeability larger, and the comprehensive performance of the iron-based amorphous nanocrystalline alloy better.
[0111] From the comparison between Example 1 and Example 3, it can be seen that the elements in the iron-based amorphous nanocrystalline alloy are the same, namely Fe, Co, Mo, Cu, Nb, Si and B, and the atomic percentage ratio of Co and Co in Example 1 is 1:1 (the atomic percentage ratio of Co and Co in Example 3 is 6:1), so the saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy strip is higher, the coercive force is smaller, and the effective magnetic permeability is larger, so that the comprehensive performance of the iron-based amorphous nanocrystalline alloy is better.
[0112] From the comparison between Example 1, Example 2 and Comparative Example 2, Comparative Example 3 and Comparative Example 5, it can be seen that the elements in the iron-based amorphous nanocrystalline alloy are the same, namely Fe, Co, Mo, Cu, Nb, Si and B, and the atomic percentage ratio of Si to B in Example 1 is 13:8, and the atomic percentage ratio of Si to B in Example 2 is 15:6 (the atomic percentage ratio of Si to B in Comparative Example 2 is 11:10, the atomic percentage ratio of Si to B in Comparative Example 3 is 8:13, and the atomic percentage ratio of Si to B in Comparative Example 3 is 13:5.5), then the saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy strip is higher, the coercive force is smaller, and the effective magnetic permeability is larger, so that the comprehensive performance of the iron-based amorphous nanocrystalline alloy is better.
[0113] By comparing Example 1 and Comparative Example 4, it can be seen that in Comparative Example 4, in addition to the elements Fe, Co, Mo, Cu, Nb, Si and B, the element Cr is also added to the iron-based amorphous nanocrystalline alloy. The saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy strip is smaller, the coercive force is larger, the effective magnetic permeability is smaller, and the comprehensive performance of the iron-based amorphous nanocrystalline alloy is deteriorated.
[0114] From the above content, it can be seen that the Fe provided in Example 2 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 15 The comprehensive performance of B6 amorphous nanocrystalline alloy is good, and its industrial production will be studied below.
[0115] The method steps of industrial production include:
[0116] a. According to the chemical formula of iron-based amorphous nanocrystalline alloy (Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 15 B6) Prepare the ingredients, weigh 180 kg of Fe-B alloy, Fe-Nb alloy, Fe-Mo alloy, Fe, Co, Si and other elements; put the raw materials into the crucible of the smelting furnace, melt the alloy raw materials and remove the slag, and smelt them twice to obtain a uniform master alloy.
[0117] b. The master alloy obtained by smelting is remelted on the weaving equipment, and the master alloy melt is sprayed onto the surface of the rotating copper roller by the single-roll melt rapid quenching method in the atmospheric environment to prepare an amorphous alloy strip with a thickness of 17 μm and a width of 35 mm. The rotation speed of the copper roller is 35 to 38 m / s.
[0118] c. The prepared iron-based amorphous strip is cut and rolled into a 40*25*15 iron core (outer diameter 40 mm, inner diameter 25 mm, height 15 mm).
[0119] d. Place the prepared magnetic core in a heat treatment furnace, evacuate to -100KPa, fill with nitrogen, turn on the power for heating, treat at 480℃ for 20min, then continue to heat to 560℃, and the heating time is 50min, continue to maintain at 560℃ for 40min, then continue to maintain at a magnetic field strength of 0.1T for 20min, then cool down to 210℃ under a magnetic field strength of 0.1T and take out of the furnace.
[0120] Fig. 9 The XRD diagram of the iron-based amorphous nanocrystalline alloy provided in Example 2 during industrial production; wherein, Fig. 9The lower line is the XRD pattern before heat treatment; the upper line is the XRD pattern after heat treatment; Fig. 9 It can be seen that the alloy before heat treatment has a typical amorphous diffuse scattering peak, and the alloy after heat treatment has obvious crystallization peaks near 2θ of 45°, 65° and 84° in the image. After comparison and analysis, the crystallized phase is α-Fe nanocrystals with bcc structure.
[0121] The magnetic permeability μ of the 40*25*15 nanocrystalline alloy core after heat treatment e Measurement, saturation magnetic induction intensity B s Measurement and coercivity H c Measurement, B s and H c The MATS magnetic material automatic testing system of Hunan Lianzhong Technology Co., Ltd. was used for testing. e The Hioki LCR tester was used for testing. The Hioki LCR tester gave the inductance value of the 40*25*15 magnetic core, which was converted and calculated to obtain the effective magnetic permeability. s 1.38T, H c It is 0.8-0.9A / m, and the effective magnetic permeability at 100kHz is about 35000, which is higher than the 1K107 alloy in the core state. The effective magnetic permeability of the 1K107 core with the same strip thickness generally does not exceed 30000. It should be noted that the effective magnetic permeability of the core is much greater than the effective magnetic permeability of the strip, so the 100kHz effective magnetic permeability value of the strip of Example 2 in Table 1 is different from the 100kHz effective magnetic permeability value of the core here, and there is no comparability.
[0122] Fig.10 The following is a photo of the industrialized production strip of the Fe-based amorphous nanocrystalline alloy provided in Example 2. 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 15 B6 amorphous nanocrystalline alloy is suitable for industrial production, and its industrial production will basically have no effect on performance. In addition, the cost of industrial raw materials in this application is lower than that of 1K107 magnetic core, which can save production costs.
[0123] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. An iron-based amorphous nanocrystalline alloy, characterized in that: The chemical formula of the iron-based amorphous nanocrystalline alloy is Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 13 B8 or Fe 75.5 Co 0.5 Mo 0.5 Cu1Nb 1.5 Si 15 B6; and the saturation magnetic induction intensity of the iron-based amorphous nanocrystalline alloy is 1.39~1.41T, the coercive force is 1.4~1.5A / m, the effective magnetic permeability is greater than 20000 at 100kHz, and the effective magnetic permeability is greater than 6000 at 1MHz.
2. An iron-based amorphous nanocrystalline alloy sheet, characterized in that: The material of the iron-based amorphous nanocrystalline alloy sheet is the iron-based amorphous nanocrystalline alloy according to claim 1.
3. The iron-based amorphous nanocrystalline alloy sheet according to claim 2, characterized in that: The thickness of the iron-based amorphous nanocrystalline alloy sheet is 17-21 μm.
4. Use of the iron-based amorphous nanocrystalline alloy sheet according to claim 2 or 3 in preparing a magnetic isolation sheet for a wireless charging device.
5. A method for preparing the iron-based amorphous nanocrystalline alloy according to claim 1, characterized in that: The iron-based amorphous nanocrystalline alloy is a strip, and the preparation method comprises: According to the contents of various elements in the chemical formula of the iron-based amorphous nanocrystalline alloy, various raw materials are weighed in mass percentage and mixed to obtain a mixed raw material; The mixed raw materials are melted to obtain alloy liquid, and the alloy liquid is sprayed onto the surface of a metal roller to obtain an iron-based amorphous alloy strip; The iron-based amorphous alloy strip is subjected to transverse magnetic annealing to obtain an iron-based amorphous nanocrystalline alloy strip.
6. The preparation method according to claim 5, characterized in that: The rotation speed of the metal roller is 30-40 m / s; The transverse magnetic annealing conditions are: heat treatment for more than 60 minutes under nitrogen protection, magnetic field of 0.05-0.1T, temperature of 540-580°C.
Citation Information
Patent Citations
Production of ultra-microcrystalline magnetic alloy
JP1990236219A